FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES FROM ELEUTHERINE BULBOSA URB. BULB EXTRACT WITH PLASTICIZER VARIATIONS - JAMALUDIN, WAHYUDIN BIN; MUTHIA, RAHMI; KARTINI, KARTINI; SETIAWAN, FINNA; JUHRAH, SITI; YULIDA, NURIL (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aimed to develop a transdermal drug delivery system from Eleutherine bulbosa Urb. bulbs as an alternative treatment with minimum side effects compared to other pain medications and increased drug penetration by determining the optimum formula(s) for transdermal patches prepared with varying plasticizer concentrations. Methods: Eleutherine bulbosa Urb. bulbs were extracted by maceration using 96% ethanol. The extract was formed into transdermal patches using the solvent casting method with six formulations (F1-F6) and different types and concentrations of the plasticizer: polyethylene glycol (PEG) 400 or dibutyl phthalate. The derived patches were then evaluated for their organoleptic properties, homogeneity, weight uniformity, thickness, folding endurance, pH level, moisture content, and acceptability (hedonic scale). Results: The evaluation of the physical properties found that all patches were dark brown, opaque, smooth-textured, and had a typical odor of the bulb’s ethanol extract and uniform weight and thickness. Other characteristics included pH ranging from 5.0±0.00 to 5.86±0.04 and a moisture content between 1.04±0.04% and 4.13±0.08%. In addition, the folding endurance was 267 times for F1 and >300 times for F2-F6. The acceptability test using the five-point hedonic scale showed different preferences for these formulas. Conclusion: F6 is the optimum formula for producing transdermal patches with excellent physical properties.